Conceptual Representations of Inclusive Education among Teachers and School Principals - Basma Frangieh; Joumana Akiki (The Journal of Studies in Language, Culture and Society)
The interventions and supports offered for students with special educational needs (SEN) in schools considered to be inclusive in Lebanon are not similar in nature and reflect a disparity in practices, which seems to be related to a varied conceptual representation, hence the usefulness of developing a clear conceptual framework to harmonize the interpretation of the implementation of inclusive schools. In the present research, we propose to analyze and discuss the conceptual representations of inclusive schools made by school principals and teachers in the public and/or private sector, our target population. A questionnaire was completed by 157 participants, followed by a content analysis. The results indicate that the conceptualization of inclusive education in Lebanon is far from being well defined. It is only partial and mostly reduced to a simple physical integration of SEN in schools. We emphasize confusion about the terms used to designate the fundamental dimensions of inclusive education. Clarification of the representations of professionals will promote an evolution in their conception and greater effectiveness in their educational practice.